2016
DOI: 10.1111/inr.12320
|View full text |Cite
|
Sign up to set email alerts
|

Nursing interventions for smoking cessation in hospitalized patients: a systematic review

Abstract: Quitting smoking can reduce lung cancers and other health problems. Nurses play an important role in helping patients to quit smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
2
16
0
2
Order By: Relevance
“…The role of health care providers is crucial for technology-based interventions such as mobile text messages or e-mails from clinicians, 99 or computer-generated expert letters, 84 or online resources supported by nurses 72 to assist high-risk smokers to reduce and cease tobacco consumption. Programs provided largely by nurses, 152 dentists, or physicians help to effectively foster patients’ initial attempts to quit and help them consider using preferred smoking cessation technology platforms. 153 – 155 For quit program developers it is often challenging to engage clinicians who are busy and not familiar with advanced technology.…”
Section: Discussionmentioning
confidence: 99%
“…The role of health care providers is crucial for technology-based interventions such as mobile text messages or e-mails from clinicians, 99 or computer-generated expert letters, 84 or online resources supported by nurses 72 to assist high-risk smokers to reduce and cease tobacco consumption. Programs provided largely by nurses, 152 dentists, or physicians help to effectively foster patients’ initial attempts to quit and help them consider using preferred smoking cessation technology platforms. 153 – 155 For quit program developers it is often challenging to engage clinicians who are busy and not familiar with advanced technology.…”
Section: Discussionmentioning
confidence: 99%
“…The tobacco cessation reality in China is that drug therapy alone or in combination with the smoking cessation interventions could enhance quit rates 27 , but pharmacotherapy is still a barrier for nursing staff in tobacco cessation services 28 . Gaining insight into pharmacotherapy administration can improve nursing students’ 5As behaviour in helping smokers quit, and tobacco cessation self-help materials are the most universal and straightforward tobacco control education resources in a clinic 29 . Although some have reported that self-help education material help smokers less than other resources 30 , nevertheless such convenient and accessible resources in internship units provide the possibility for students to improve their behaviour towards helping patients quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, resources to support smoking cessation during residential therapy are mostly limited to one brief counselling appointment, ranging from 5 min to 2 h, self-help materials and supplementary follow-up calls after discharge. For a detailed overview, see Kazemzadeh et al and Rigotti et al [31,32]. Different scientific reviews have shown brief counseling interventions to be cost-effective as first-line therapy for smokers, yet long-term abstinence rates remain rather low [26,[31][32][33][34][35].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…For a detailed overview, see Kazemzadeh et al and Rigotti et al [31,32]. Different scientific reviews have shown brief counseling interventions to be cost-effective as first-line therapy for smokers, yet long-term abstinence rates remain rather low [26,[31][32][33][34][35]. There is reason to doubt that a brief therapy session allows for enough support of motivational and volitional processes as well as development and evaluation of new behavioral patterns for long-term abstinence.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%